Frequency of periodontal pathogens and Helicobacter pylori in the mouths and stomachs of obese individuals submitted to bariatric surgery: a cross-sectional study - André Luiz PATARO; Sheila Cavalca CORTELLI; Mauro Henrique Nogueira Guimarães ABREU; José Roberto CORTELLI; Gilson Cesar Nobre FRANCO; Davi Romeiro AQUINO; Luis Otavio Miranda COTA; Fernando Oliveira COSTA
ABSTRACT Objectives This cross-sectional study compared the frequency of oral periodontopathogens and H. pylori in the mouths and stomachs of obese individuals with or without periodontitis submitted to bariatric surgery. Material and Methods One hundred and fifty-four men and women aged 18-65 were conveniently distributed into four groups. Two groups were composed of individuals who underwent bariatric surgery with (BP) (n=40) and without (BNP) (n=39) periodontitis and two obese control groups with (CP) (n=35) and without (CNP) (n=40) periodontitis. The oral pathogens Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Parvimonas micra, Treponema denticola, Tannerella forsythia, Campylobacter rectus, and Helicobacter pylori were detected by a polymerase chain reaction technique using saliva, tongue and stomach biopsy samples. Results Statistical analysis demonstrated that periodontopathogens were highly frequent in the mouth (up to 91.4%). In the bariatric surgically treated group, orally, P. gingivalis, T. denticola and T. forsythia were more frequent in periodontitis, while C. rectus was more frequent in non-periodontitis subjects. Stomach biopsies also revealed the high frequency of five oral species in both candidates for bariatric surgery (91.6%) and the bariatric (83.3%) groups. H. pylori was frequently detected in the mouth (50.0%) and stomach (83.3%). In the stomach, oral species and H. pylori appeared in lower frequency in the bariatric group. Conclusions Obese individuals showed high frequencies of periodontopathogens and H. pylori in their mouths and stomachs. Bariatric surgery showed an inverse microbial effect on oral and stomach environments by revealing higher oral and lower stomach bacterial frequencies.